Odpowiedzi

Najlepsza Odpowiedź!
2010-03-14T16:42:08+01:00
A) 2(x-1/2)-x+3=3
2x -1 -x + 3 = 3
x = 1

spr:
2(1 - 1/2) -1 + 3 = 3
2 - 1 -1 +3 = 3
3=3

b) 0=3-(2x+1)
0 = 3 - 2x - 1
2x = 2
x = 1

spr:
0 = 3-(2*1+1)
0 = 3 - 2 -1
0 = 0

c) 0=(x-1)-(3x-5)
0 = x - 1 -3x + 5
2x = 4
x = 2

spr:
0 = (2 - 1) - (3*2 - 5)
0 = 1 - 6 + 5
0 = 0

d) (-1/2x+1)+1 1/2x=3
-1/2x + 1 +1 1/2x = 3
x = 2

spr:
(-1 + 1) + 3 = 3
3 = 3

e) 3(1-x)-(1-2x)=9
3 - 3x -1 + 2x = 9
-x = 7
x = -7

spr:
3 + 21 - 1 - 14 = 9
9 = 9

f) 0,5(2-4x)=3-x
1 - 2x = 3 - x
- x = 2
x = -2

spr:
1 + 4 = 3 + 2
5 = 5
14 4 14